PENGARUH PENGGUNAAN METODE TOKEN EKONOMI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS IV DI SD KARANGASEM 1 SURAKARTA - Sholikhah, Azzahra Mar'atush; Prihastari, Ema Butsi; Hanafi, Muhammad Faruq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the significant effect of the Token Economics method on students' learning motivation in mathematics, specifically multiplication and division story problems, for fourth-grade students at SD Negeri Karangasem 1 Surakarta in the 2025/2026 academic year. The research method used was quantitative with a One-Group Pretest-Posttest Design. The population of this study was fourth-grade students at SDN Karangasem 1 Surakarta, with a saturated sample of 28 students from class IVA. The primary data collection technique was a closed-ended questionnaire with four Likert-type answers to measure learning motivation variables, supported by observation and documentation techniques. Instrument validity was tested using the Product Moment correlation formula, and its reliability showed a Cronbach's Alpha coefficient of 0.829 (Very Reliable Category). The results of the descriptive statistical analysis showed an average (mean) learning motivation score before the treatment (pretest) of 73.46, increasing to 83.54 in the posttest. Hypothesis testing was conducted using a parametric Paired Sample T-Test using SPSS. The Paired Sample T-Test output showed a Sig. (2-tailed) value of 0.000. Since the significance value of 0.000 < 0.05, the t-test was rejected and the t-test was accepted. It can be concluded that the implementation of the Token Economy method has a significant effect on students' learning motivation in solving multiplication and division math story problems. The implications of this study indicate that classroom management through structured external reinforcement can transform passive behavior patterns into active, competitive, and enthusiastic ones.